Multicenter Cohort Study, With a Nested Randomized Comparison, to Examine the Cardiovascular Impact of Preterm Preeclampsia. Issue 5 (November 2021) - McCarthy, Fergus P.; O'Driscoll, Jamie M.; Seed, Paul T.; Placzek, Anna; Gill, Carolyn; Sparkes, Jenie; Poston, Lucilla; Marber, Mike; Shennan, Andrew H.; Thilaganathan, Basky; Leeson, Paul; Chappell, Lucy C.
Abstract : This study evaluated whether planned early delivery would ameliorate cardiovascular dysfunction 6 months postpartum, compared with usual care with expectant management, in women with late preterm preeclampsia. We conducted a mechanistic observational study in women with preterm preeclampsia between 34 +0 and 36 +6 weeks' gestation, nested within a randomized controlled trial of planned early delivery versus expectant management (usual care), in 28 maternity hospitals in England and Wales. Women were followed up 6 months postpartum with cardiovascular assessments. The primary outcome was a composite of systolic and diastolic dysfunction (by 2009 and 2016 definitions of diastolic dysfunction). Between April 27, 2016, and November 30, 2018, 623 women were found to be eligible, of whom 420 (67%) were recruited. One hundred thirty-three women were randomized to planned delivery, 137 women were randomized to expectant management within the trial, while 150 women received expectant management outside of the trial. 321 (76.4%) completed their 6 month echocardiography assessment. 10% (31/321) had a left ventricular ejection fraction <55% while 71% (229/321) remained hypertensive. There were no differences in the primary outcome between the 2 randomized groups (planned delivery versus expectant management) using either the 2009 (risk ratio, 1.06 [95% CI, 0.80–1.40]) or 2016 definitions (risk ratio, 0.78 [0.33–1.86]). In conclusion, we demonstrated that late preterm preeclampsia results in persistence of hypertension in the majority and systolic LV dysfunction in 10%, of women 6 months postpartum. Planned early delivery does not affect these outcomes. Preeclampsia is not a self-limiting disease of pregnancy alone. Abstract : Supplemental Digital Content is available in the text.